The Impact of the Medicaid Health Care-Associated Condition Program on Mediastinitis Following Coronary Artery Bypass Graft - Hsu, Heather (Infect Control Hosp Epidemiol, 2018)
OBJECTIVE: In 2012, the Centers for Medicare and Medicaid Services expanded a 2008 program that eliminated additional Medicare payment for mediastinitis following coronary artery bypass graft (CABG) to include Medicaid. We aimed to evaluate the impact of this Medicaid program on mediastinitis rates reported by the National Healthcare Safety Network (NHSN) compared with rates of a condition not targeted by the program (deep space surgical site infection [SSI] after knee replacement). DESIGN: interrupted time series with comparison group. METHODS: We included surveillance data from non-federal acute care hospitals participating in NHSN and reporting CABG or knee replacement outcomes from 1/2009–6/2017. We examined the Medicaid program’s impact on NHSN-reported infection rates, adjusting for secular trends. Data analysis used generalized estimating equations with robust sandwich variance estimators. RESULTS: During the study period, 196 study hospitals reported 273,984 CABGs to NHSN, resulting in 970 mediastinitis cases (0.35%); 294 hospitals reported 555,395 knee replacements, with 1,751 resultant deep space SSIs (0.32%). There were no significant changes in incidence of either condition during the study. Mediastinitis models showed no effect of the 2012 Medicaid program on either secular trend during the post- vs. pre-program time periods (p-value=0.70) or immediate program effect (p-value=0.83). Results were similar in sensitivity analyses when adjusting for hospital characteristics, restricting to hospitals with consistent NHSN reporting, or incorporating a program implementation roll-in period. Knee replacement models also showed no program effect. CONCLUSIONS: The 2012 Medicaid program to eliminate additional payments for mediastinitis following CABG had no impact on reported mediastinitis rates.